Leveraging Nation Branding Strategies to Amplify Creative Exports: A Managerial Perspective on Global Soft Power and Cultural Commodity Value - Sidiq, Asah Wiari (Smart International Management Journal, 2026)
Nation branding plays a strategic role in enhancing the competitiveness of creative exports through strengthening cultural identity and global perception, yet primary canals frequently suffer structural failures due to excessive dewatering rates. This study aims to determine the safe water level drawdown velocity for the Sindupraja Main Canal in the Rentang Irrigation District to mitigate bank slope instability. This study adopts a quantitative approach using secondary data and econometric analysis to evaluate the influence of nation branding on creative export performance and slope stability analysis utilizing secondary geotechnical data from the Ministry of Public Works and Housing (PUPR) alongside global economic indicators. Simulation results indicate that the alluvial clay at the study site exhibits an 85.00% lag in pore water pressure dissipation, where drawdown rates exceeding 0.75 m/day force the Factor of Safety (FS) down to 1.05 (failure category). Correlation analysis further reveals that irrigation reliability contributes 28.30% to the export value of agriculture-based creative commodities. It is concluded that restricting the maximum drawdown rate to 0.30 m/day is essential for maintaining structural integrity and the sustainability of the rural creative economy. This research offers a scientific contribution by integrating unsaturated geotechnical parameters with national soft power managerial strategies.